2007
DOI: 10.1002/chem.200601649
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Cation Migration Above the Diimine π‐System of Solvent Coordinated dpp‐BIAN Sodium Aluminum Complexes (dpp‐BIAN=1,2‐Bis[(2,6‐diisopropylphenyl)imino]acenaphthene)

Abstract: The reactions of the disodium salt of the 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene (dpp-BIAN) ligand with one equivalent of Me2AlCl in diethyl ether, toluene, and benzene produced the complexes [Na(Et2O)2(dpp-BIAN)AlMe2] (1), [Na(eta6-C7H8)(dpp-BIAN)AlMe2] (2) and [Na(eta6-C6H6)(dpp-BIAN)AlMe2] (3), respectively. Recrystallization of 1 from hexane afforded solvent-free [{Na(dpp-BIAN)AlMe2}n] (4) or [Na(Et2O)(dpp-BIAN)AlMe2] (5) depending on the temperature of the solvent. The molecular structures of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Although they are in different environments, the newly formed Al(1)C(67) (1.997(3) Å) and Al(2)C(68) bonds (1.992(3) Å) are almost identical in length. These values are comparable to other reported Al III C(sp 3 ) bond lengths in LAlMe 2 compounds (1.947(4)–2.010(4) Å),10, 11 but are somewhat longer than Al III C(sp 2 ) bond lengths in complex L′Al(CR 1 CHR 2 )(CCR 3 ) 11…”
Section: Resultssupporting
confidence: 89%
“…Although they are in different environments, the newly formed Al(1)C(67) (1.997(3) Å) and Al(2)C(68) bonds (1.992(3) Å) are almost identical in length. These values are comparable to other reported Al III C(sp 3 ) bond lengths in LAlMe 2 compounds (1.947(4)–2.010(4) Å),10, 11 but are somewhat longer than Al III C(sp 2 ) bond lengths in complex L′Al(CR 1 CHR 2 )(CCR 3 ) 11…”
Section: Resultssupporting
confidence: 89%
“…Keywords: EPR spectroscopy · gallium · metal-metal interactions · N ligands · structure elucidation · zinc ([dpp-bian] nÀ , n = 1, 2). [7] Animated by the successful synthesis of the dizinc compound 1, we suggested that the dppbian ligand may also be able to stabilize homonuclear bonds of Group 13 metals and possibly even heteronuclear bonds between Group 12 and Group 13 metals. The isolation of both, dpp-bian-supported digallium and dpp-bian-supported zinc-gallium compounds confirmed this suggestion.…”
Section: With K 3 a C H T U N G T R E N N U N G [Dpp-bian] And The Hementioning
confidence: 96%
“…The redox non‐innocent behavior of Ar‐BIAN compounds has been evident since the beginning and in the last decade a number of complexes has been reported, mainly by the groups of Fedushkin and Schumann, in which the BIAN ligand has been reduced by up to four electrons 63. 7780 However, this chemistry has been mostly limited to sterically encumbered ligands (e.g., 2,6‐ i Pr 2 C 6 H 3 ‐BIAN) and little quantitative information on the electronic effect of different substituents is available 8183…”
Section: Introductionmentioning
confidence: 99%